Current practices, problems and policies in fuelwood management : a case study in Thimphu, Bhutan - Jimba, Karma; Lantican, Celso B.; Apisit Eiumnoh; Worah, Sejal; Asian Institute of Technology Fellowship; Japan Government (Bangkok : Asian Institute of Technology, 1996)
Fuelwood, being the mainstay of poor people, is a major concern worldwide because of forest degradation and is also the concern of Bhutanese people. For instance, per capita consumption of fuelwood was approximately 3.0 m3 in Thimphu District (Bhutan) as per a swvey by the Forestiy Se1vices Division, Thimphu (1994). The information on fuelwood issues is limited despite much concern. Inadequate information was the reason for not taking fuelwood issues into energy planning of Bhutan with enough degree of se1iousness. Therefore, this research is intended to generate a piece of valuable inf01mation for the natural resources planners. The objectives achieved were: 1. CmTent laws and policies governing fuelwood management reviewed. 2. The dependency patterns, cunent mechanisms and systems of supply and demand identified. On analysis it revealed mral consumption to be 6.11 kg/head/day and urban consumption to be 2.21 kg/head/day. 3. Existing natural fuelwood resources stock assessed. Considering the cmrnnt consumption rate and existing natural fuelwood resources, scenarios of fuelwood situation by 2040 are projected. 4. Recommendations made upon findings of this study for sustainable management of fuelwood resources in the district. Reviewed legislation and fuelwood development policies were cross-refened to reviews made by other agencies such as international organizations, projects, expe1ts and NGOs to fotm an extensive review. Rapid Rural Appraisal (RRA) methodology was used for rural data collection. Geographical lnfo1mation System (GIS) and maps were used for fuelwood stock assessment in nature that was groundtmthed for accuracy. Though the RRA data was subjective, here it's assumed that data collected were close to accurate. Hence, inferential statistics were applied for analysis for making broader generalizations.
Thesis (M. Eng.) - Asian Institute of Technology, 1996
A thesis submitted in paitial fu1fillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Keywords: Fuelwood -- Bhutan -- Thimphu